The Influence of Self Efficacy, Goal Orientation and Learning Behavior on Accounting Student Learning Achievement with Gender as an Intervening Variable (Study on Accounting S1 Students, Muhammadiyah University of Sidoarjo) - Fachrudin Arozy; Sigit Hermawan (Universitas Muhammadiyah Sidoarjo, 2023)
In the process of developing an industry that is developing, one of the majors needed is prospective workers majoring in accounting. The purpose of carrying out this research is to find out whether the variables of self-efficacy, Goal Orientation, learning behavior affect learning achievement directly and are mediated by gender in accounting students at Muhammadiyah University of Sidoarjo. The Slovin formula is a sampling technique taken to determine the sample in this research so that this study found a sample of 147 respondents from accounting students at the Muhammadiyah University of Sidoarjo then primary data which is the source of data in this study was tabulated and processed with the help of SmartPLS then a set of test tools to support hypothesis by bootstrapping partial least square test. That the results obtained in the analysis carried out are self-efficacy can affect student learning achievement, goal orientation affects student learning achievement, learning behavior can affect student learning achievement, self-efficacy can affect learning achievement with gender as an intervening variable, goal orientation is not able to affect learning achievement through gender as an intervening variable in students, learning behavior is not able to affect learning achievement through gender as an intervening variable in Accounting Students at Muhammadiyah University of Sidoarjo.